The impact of functionalized CNT in the network of sodium alginate-based nanocomposite beads on the removal of Co(II) ions from aqueous solutions - Karkeh-abadi, Fatemeh; Saber-Samandari, Samaneh; Saber-Samandari, Saeed (Elsevier Science Bv, 2016)
Significant efforts have been made to develop highly efficient adsorbents to remove radioactive Co(II) ion pollutants from medical and industrial wastewaters. In this study, amide group functionalized multi-walled carbon nanotube (CNT-CONH2) imprinted in the network of sodium alginate containing hydroxyapatite, and new nanocomposite beads were synthesized. Then, they were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction analysis (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The prepared nanocomposite beads were used as an adsorbent of Co(II) ions from an aqueous solution. The presence and distribution of Co(II) ions in the surface of the nanocomposite beads was confirmed using FESEM, EDS and metal mapping analysis. The effect of various experimental conditions such as time, pH, and initial concentration of the adsorbate solution and temperature on the adsorption capacity of the nanocomposite beads were explored. The maximum Co(II) ions adsorption capacity of the prepared nanocomposite beads with the largest surface area of 163.4 m(2) g(-1) was 347.8 mgg(-1) in the optimized condition. The adsorption mechanism followed a pseudo-second-order kinetic model. Furthermore, the Freundlich appears to produce better fit than the Langmuir adsorption isotherm. Finally, thermodynamic studies suggest that endothermic adsorption process of Co(II) ions is spontaneous and thermodynamically favorable. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Functionalized CNT; Water treatment; Nanocomposite beads; Metal removal